Mechanics and physiology of animal swimming - Maddock, Linda; Bone, Q.; Rayner, Jeremy M. V. (Cambridge University Press, 1994)
Aquatic organisms swim in a variety of ways, from jet propulsion to ciliary action: they swim at a wide range of speeds and span a vast size range, from bacteria to protists, to the largest whales. One of the most fascinating aspects of aquatic locomotion is the remarkable sets of adaptations that have been evolved for different purposes. This volume brings together research on a wide range of swimming organisms, with an emphasis on the biomechanics, physiology and hydrodynamics of swimming in or on water. Several chapters deal with different aspects of fish swimming, from the use of different 'gaits' to the operation of the locomotor muscles. All chapters are by recognized authorities in their different fields, and all are accessible to biologists interested in aquatic locomotion